2022
DOI: 10.1177/17449871221088791
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative systematic review and meta-aggregation of the experiences of men diagnosed with chronic lymphoedema

Abstract: Background Lymphoedema is a chronic condition that is estimated to affect up to four people per 1000 of the UK population with this increasing with age. Men account for up to 20% of lymphoedema service caseloads with research focussing upon women affected. Aims To retrieve primary qualitative research on the experiences of men with chronic lymphoedema. Methods A qualitative review was undertaken using the Joanna Briggs Institute (JBI) meta-aggregation method. A search strategy was applied to 12 databases, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Conversely, the control group experienced improvement in only some symptoms—swelling, leg heaviness, and pain—without statistical significance. Given that individuals with lower limb lymphedema often struggle with prolonged standing or walking,30,31 the utilization of unstable-soled footwear might facilitate these activities. Our study's intervention group demonstrated a reduction in the prevalence of cramps and paresthesias, potentially contributing to eased standing and walking.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the control group experienced improvement in only some symptoms—swelling, leg heaviness, and pain—without statistical significance. Given that individuals with lower limb lymphedema often struggle with prolonged standing or walking,30,31 the utilization of unstable-soled footwear might facilitate these activities. Our study's intervention group demonstrated a reduction in the prevalence of cramps and paresthesias, potentially contributing to eased standing and walking.…”
Section: Discussionmentioning
confidence: 99%